2009
DOI: 10.1074/jbc.m109.048157
|View full text |Cite
|
Sign up to set email alerts
|

Saccharomyces CDK1 Phosphorylates Rad53 Kinase in Metaphase, Influencing Cellular Morphogenesis

Abstract: Rad53 is an essential protein kinase governing DNA damage and replication stress checkpoints in budding yeast. It also appears to be involved in cellular morphogenesis processes. Mass spectrometry analyses revealed that Rad53 is phosphorylated at multiple SQ/TQ and at SP/TP residues, which are typical consensus sites for phosphatidylinositol 3-kinase-related kinases and CDKs, respectively. Here we show that Clb-CDK1 phosphorylates Rad53 at Ser 774 in metaphase. This phosphorylation event does not influence the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(35 citation statements)
references
References 25 publications
2
31
0
2
Order By: Relevance
“…On one hand, it is possible that Isc1 controls morphological functions of Rad53 function, which in turn, may control Swe1, and ultimately control Cdk1. On the other hand, Rad53 has phosphorylation targets of Cdk1, and a specific amino acid residue on Rad53 has been implicated in its role in certain aspects of morphogenesis (Diani et al 2009). It has been shown that both Swe1 and Cdk1 control HU-mediated G2/M arrest of isc1D cell sensitivity ), and we show here that they control morphological aberrations of isc1D cells under HU stress.…”
Section: Discussionsupporting
confidence: 48%
See 4 more Smart Citations
“…On one hand, it is possible that Isc1 controls morphological functions of Rad53 function, which in turn, may control Swe1, and ultimately control Cdk1. On the other hand, Rad53 has phosphorylation targets of Cdk1, and a specific amino acid residue on Rad53 has been implicated in its role in certain aspects of morphogenesis (Diani et al 2009). It has been shown that both Swe1 and Cdk1 control HU-mediated G2/M arrest of isc1D cell sensitivity ), and we show here that they control morphological aberrations of isc1D cells under HU stress.…”
Section: Discussionsupporting
confidence: 48%
“…A third possibility is that treatment of isc1D cells with HU may also lead to Swe1 accumulation inducing Cdk1 phosphorylation, which can affect Rad53 phosphorylation. Cdk1-dependent Rad53 phosphorylation already has been implicated in morphogenesis in yeast (Diani et al 2009). All three pathways may be used simultaneously to affect cell morphology also.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations